Pengembangan Pembelajaran Matematika Berbasis Tutor Sebaya Dengan It Pada Siswa Sd Negeri Kemasan I Serengan Surakarta Tahun 2016/2017 - Suhartadi, Pius Franciscus Sales Suryo Asri, Dr.Djalal Fuadi, MM (2017)
Mathematics is one of the main subjects in the K13 in elementary school. Math must be mastered by the students as early as possible in the face of changing circumstances and the ever-evolving technology. To transfer the necessary mathematics to students learning methods that interest. One of the methods is the appropriate method peer tutors. This study examines the mathematics teachers do this time and the development of peer tutoring based learning with IT in SDN Kemasan I Surakarta. The purpose of this study is to describe the mathematics before action research, determine eligibility based peer tutoring mathematics learning using IT, as well as test the effectiveness of peer tutoring based math learning using IT media. This study was conducted for students of class V. This study uses research methods research and development (R & D) which is a product development activities are effective for use. Do lesson planning, implementation, testing, and refinement. Further testing of the effectiveness of student learning during the implementation of peer tutoring program in a class by comparing the results of student achievement before and after participating in the peer tutoring program in the classroom. The results of this study occurred average value of student learning outcomes have also been increased initially 65.33, on the stages I to 71.25, and at what stage II in 76.62.